2000
DOI: 10.1017/s0010417500003303
|View full text |Cite
|
Sign up to set email alerts
|

Kuria Cattle Raiding: Capitalist Transformation, Commoditization, and Crime Formation Among an East African Agro-Pastoral People

Abstract: Among the agro-pastoral Kuria people, whose population straddles the border between Tanzania and Kenya, many young men are actively engaged in an illicit livestock trade in which cattle stolen in Tanzania—from other Kuria, as well as from neighboring peoples such as the Luo, Ngoreme, and Maasai—are sold to buyers, mainly butchers, inside Tanzania or else are run across the border for cash sale in neighboring Kenya. Kenya is a more affluent country than Tanzania—consequently, the demand for beef is greater ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…It is not a coincidence that geography and social problems converge here; remote and marginal areas are attractive environments for certain types of violence and criminal behaviour. This is in line with Fleisher (2000), who observed that in southern Kenya no effective opposition to cattle raiding exists among herding communities because of recurring clan warfare. While alluding to a similar ethnographic account in western Kenya, Anderson (1993: 865) observes that among the Kalenjin community, allegedly, the cattle-rustling activities of the moran (a Maasai word for warriors) are considered rather a ‘sport’ and not a crime.…”
Section: Example Of Violent Conflict From Northern Kenyasupporting
confidence: 89%
“…It is not a coincidence that geography and social problems converge here; remote and marginal areas are attractive environments for certain types of violence and criminal behaviour. This is in line with Fleisher (2000), who observed that in southern Kenya no effective opposition to cattle raiding exists among herding communities because of recurring clan warfare. While alluding to a similar ethnographic account in western Kenya, Anderson (1993: 865) observes that among the Kalenjin community, allegedly, the cattle-rustling activities of the moran (a Maasai word for warriors) are considered rather a ‘sport’ and not a crime.…”
Section: Example Of Violent Conflict From Northern Kenyasupporting
confidence: 89%
“…This is in line with Fleisher's observation of no effective opposition to cattle raiding in Southern Kenya, while evidence of recurring clan warfare exists among herding communities. 42 This locally legitimises cattle raiding in its function as a training opportunity for young men. Raiding reinforces a climate of insecurity and lawlessness that is needed to effectively raid other ethnic groups in the absence of effective law enforcement.…”
Section: On Insecuritymentioning
confidence: 99%
“…This emphasis on raiding as central to social excellence and identity is in no way exceptional. It can be found in many accounts of pastoral nomads (see e.g., Fleisher 2000:751; Anderson 1986:402; Sweet 1965), and it is often cited, by the concerned themselves, as one of the elements that distinguishes them from their neighbors: the couple Nuer–Dinka is probably the best-known example here (Sahlins 1961:340; Kelly 1985). In all these contexts, raids mark relations with outsiders (although they might in fact ultimately turn raided outsiders into insiders), and they are thus seen to be clearly and fundamentally different from theft.…”
Section: Raiding and Theftmentioning
confidence: 99%